1985
DOI: 10.1159/000173959
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Biochemical Aspects of Pheochromocytoma

Abstract: In 110 patients the diagnosis of pheochromocytoma was established by biochemical tests. These patients displayed various patterns of urinary and plasma catecholamines and their metabolites. The estimation of urinary methoxycatecholamines proved the most useful screening procedure. In patients with equivocal biochemical results the clonidine suppression test appeared to be a useful diagnostic tool. Clinical analysis displayed a bizzare course and unusual symptoms and signs in some patients. Computerized tomogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
2

Year Published

1987
1987
2010
2010

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 6 publications
2
5
0
2
Order By: Relevance
“…However, all patients with pheochromocytoma, regardless of their blood pessure patterns, had urinary TM values above 5485 nmol/day as NM (1000 /xg/24 h), well above the upper limit of normal. Thus, this study reaffirms the usefulness of determining urinary TM in the diagnosis of pheochromocytoma (1,2,(16)(17)(18). Remine et al (19) reported that 96% of pheochromocytoma patients could be diagnosed by the determination of urinary TM, 79% could be diagnosed by the determination of urinary CA, and only 53% could be diagnosed by the determination of plasma CA.…”
Section: Discussionsupporting
confidence: 80%
“…However, all patients with pheochromocytoma, regardless of their blood pessure patterns, had urinary TM values above 5485 nmol/day as NM (1000 /xg/24 h), well above the upper limit of normal. Thus, this study reaffirms the usefulness of determining urinary TM in the diagnosis of pheochromocytoma (1,2,(16)(17)(18). Remine et al (19) reported that 96% of pheochromocytoma patients could be diagnosed by the determination of urinary TM, 79% could be diagnosed by the determination of urinary CA, and only 53% could be diagnosed by the determination of plasma CA.…”
Section: Discussionsupporting
confidence: 80%
“…In rare instances, pheochromocytoma causes sudden peripheral ischemia, resulting in necrosis or gangrene [74][75][76][77]. In most cases, this ischemia is due to extreme vasoconstriction or diffuse arterial vasospasms induced by catecholamine overload.…”
Section: Acute Peripheral Ischemiamentioning
confidence: 99%
“…Patients may also present with intestinal pseudo-obstruction [92,93], abdominal distension [94], severe paralytic ileus [74,89,95,96], dilated small bowel loops [97], or megacolon [94,98]. The latter may be complicated by enterocolitis [98,99], volvulus or colonic rupture [100], and fecal peritonitis [101].…”
Section: Gastrointestinal Emergenciesmentioning
confidence: 99%
“…Pheochromocytomas are relatively uncommon in children, but sometimes can be incidentally observed, especially in adolescents with hypertension. A calcified pheochromocytoma has been described in single case reports 9 .…”
Section: Discussionmentioning
confidence: 99%